How to Communicate Lateran IV in 13th Century Ireland: Lessons from the Liber Exemplorum (c.1275) - Ryan, Salvador (Religions, 2018)
The Liber Exemplorum, a collection of preachers' tales, was compiled c.1275 by an English Franciscan working in Ireland, and is the earliest Franciscan example of its type. Out of 213 exempla which survive in this manuscript, some 26 of these are found in no other source, and are drawn either from the compiler's own experience or from his having heard of them second hand; these often mention Irish place names and feature Irish Christians as the main protagonists. The collection was compiled some 60 years after the calling of the Fourth Lateran Council, whose decrees would significantly shape the lives of medieval Christians for centuries. This article examines the manner in which some of the principal concerns of Lateran IV appear prominently as themes in this collection of preachers' tales, and, furthermore, how such tales played a crucial role in the popular dissemination of the reforms envisaged by the council fathers. The tales themselves also offer a unique window on popular religious practice and ideas, both real and imagined, in late-13th-century Ireland.